EP116/#725 Low-grade p53abn endometrial carcinomas exist and are associated with a high risk of recurrence, even in low-stage disease. (4th December 2022) - Jamieson, Amy; Vermij, Lisa; Carlson, Joseph; Howitt, Brooke; Ip, Phillip; Lax, Siguard; Mccluggage, Glenn; Singh, Naveena; Mcalpine, Jessica; Nout, Remi; Creutzberg, Carien; Gilks, Blake; et al.
Abstract : Objectives: p53abn endometrial cancer (EC) is associated with a high risk of recurrence. Molecular classification of EC cohorts has shown that ~5% of low-grade endometrioid EC (EEC) are p53abn. There is debate whether these are misclassified glandular variants of serous EC, and whether the risk of recurrence justifies adjuvant therapy. Here, we aim to determine if blinded expert pathology review classifies p53abn EC as low-grade EEC and assess risk of recurrence. Methods: p53abn low-grade EEC from retrospective cohorts and the PORTEC-1&2 trials were included. Review of histotype and grade was performed by six expert gynaecopathologists, blinded to molecular class and study aim. Cases were considered low-grade p53abn EEC if ≥1 expert assigned it as such. Kaplan-Meier's method and the log-rank test were used for survival analysis. Results: 72 low-grade p53abn EEC were included. ≥1 pathologists assigned low-grade EEC in 53 (73.6%), and ≥50% of pathologists in 36 (50%) cases. The 5-year recurrence-rate was 31.9% (95%CI: 19.4–42.5%) and 29.5% (95%CI 16.9–40.3%) among those (N=67) with stage I disease. Within stage I and those assigned by ≥1 pathologist as low-grade p53abn EEC, the 5-year recurrence-rate was 22.9% (95%CI: 9.2–34.6%); 21.2% (95%CI: 2.3%-36.4%) in stage IA and 26.3% (95%CI: 3.6–43.7%) in stage IB ( figure 1 ). Conclusions: We show the p53abn molecular subtype of EC encompasses a subset of low-grade EEC which are associated with a substantial risk of disease recurrence. Assessment of molecular classification in all low-stage low-grade ECs will enable detection of patients with p53abn EC who may benefit from adjuvant therapy.